How landscape factors relate to biodiversity-economic performance in an Estonian grassland-rich region - Takamasa Nishizawa; Johannes Schuler; Miguel Villoslada; Claudia Bethwell; Michael Glemnitz; Maaria Semm; Monika Suškevičs; Kalev Sepp; Rando Värnik; Florian Kestel; Meelis Ots; Peter Zander; et al. (Environmental Management, 2026)
Halting biodiversity loss on semi-natural grassland has become a key priority of agri-environmental policies in Estonia. However, to what extent current schemes are sufficient to achieve biodiversity targets and the role of landscape factors is still insufficiently understood in this context. This study explored trade-offs between profitability and biodiversity conservation across heterogeneous Estonian agricultural landscapes to support the development of economically effective grassland conservation schemes. To this end, we selected twelve ‘landscape windows’ in a grassland-rich region that represent a gradient of several biodiversity-related landscape factors (semi-natural grassland share, yield potential and landscape complexity). Profitability was assessed using total gross margins derived from a bio-economic model, while biodiversity was evaluated through habitat values for different bird species, based on model outputs. We found that landscapes with higher complexity, which currently maintain higher biodiversity levels, had a corresponding lower farm profitability. In particular, landscape windows dominated by semi-natural grasslands with low grass yields showed the lowest profitability, largely due to limited capacity for feeding beef cattle. In contrast, arable land-dominated landscapes (i.e. those with higher yield potential) demonstrated considerable potential for enhancing biodiversity outcomes while minimising profitability losses. Therefore, conservation policy faces two main challenges: 1. preserving landscapes with high biodiversity value against further decline in profitability, 2. highlighting the need to explore and design biodiversity measures in arable-dominated landscapes that could improve biodiversity outcomes while limiting impacts on farm profitability. This study illustrates that landscape factors deserve greater attention in conservation planning.

Participatory Scenario Design to Support Ex-ante Biodiversity and Ecosystem Services Assessments in Four European Agricultural Case Studies - Katrin Karner; Monika Suškevičs; Florian Danzinger; Sonja Kay; Claudia Bethwell; Noëlle Klein; Takamasa Nishizawa; Johannes Schuler; Michael Glemnitz; Peter Zander; Tobias Conradt; Kalev Sepp; et al. (Environmental Management, 2026)
Anticipating future socioeconomic conditions through scenarios supports effective land-use planning and management that safeguards biodiversity and ecosystem services (BES). This study introduces a novel participatory scenario development protocol to design consistent, nested regional scenarios tailored for BES assessments of agricultural land-use. The protocol is applied in four European case studies (subnational regions in Austria, Estonia, Germany, and Switzerland), combining regional narratives with quantitative developments aligned with the Shared Socioeconomic Pathways for European agri-food systems for 2050 (Eur-Agri-SSPs). Two innovative scenario components are introduced: (i) land-use and management practices and (ii) land-use-biodiversity actions, including private and public instruments. These components are typically neglected in larger-scale scenario applications. Despite shared European boundary conditions from the Eur-Agri-SSPs, the regional scenarios exhibit substantial variation, driven by current land-use structures and stakeholder input. Scenario elements, shaped by existing funding schemes and socioeconomic contexts, vary substantially across scenarios and regions. Examples include the share of organic farms and the level of payments for agri-environment-climate measures. In Münsterland (Germany) and Lääne County (Estonia), current agri-environment payments are significantly lower than in Schwarzbubenland (Switzerland) or the Wienerwald (Austria), and this is reflected in the SSP1 (“..sustainable paths”) and SSP2 (“..established paths”) scenarios. This study demonstrates the value of regional extensions of the SSP framework, grounded in participatory processes, to support context-specific BES assessments. It contributes to scenario research by presenting key challenges and recommendations for nested participatory scenario design and by bridging the gap between global and continental frameworks and subnational implementation needs.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Spatial arrangement of intercropping impacts natural enemy abundance and aphid predation in an intensive farming system - Jennifer B. Thompson; Thomas F. Döring; Sonoko Dorothea Bellingrath-Kimura; Kathrin Grahmann; Michael Glemnitz; Moritz Reckling (Agriculture, Ecosystems & Environment, 2025)

Modelling Alternative Economic Incentive Schemes for Semi-Natural Grassland Conservation in Estonia - Takamasa Nishizawa; Johannes Schuler; Claudia Bethwell; Michael Glemnitz; Maaria Semm; Monika Suškevičs; Laura Hämäläinen; Kalev Sepp; Rando Värnik; Sandra Uthes; Joachim Aurbacher; Peter Zander (Environmental Management, 2024)
Semi-natural grasslands (SNGLs) in Estonia are threatened by abandonment. This threat is leading to concerns about the degradation of biodiversity within grassland communities. Despite the high relevance of economic incentives in this context, how such incentives influence land managers’ decision-making regarding the agricultural use of SNGLs has not been investigated. To obtain its socio-ecological implications for policy-making, we developed regionally specific agricultural scenarios (compensation payments, livestock capacity, hey export, and bioenergy production) and an interdisciplinary modelling approach that made it possible to simulate agricultural land use changes through land managers' responses to varied economic conditions. Through this approach, we found that some economic factors hampered the use of SNGLs: the moderate profitability of beef production, labour shortages, and the relatively high profitability of mulching. We observed a positive relationship between SNGLs and habitat suitability for breeding and feeding birds. However, due to the high maintenance costs of SNGLs, the modelling results indicated that increasing the use of SNGLs through public budgets caused crowding-out effects, i.e., the deteriorating market integration of regional agriculture. This study emphasises the need for policy measures aimed at cost-effective, labour-efficient management practices for SNGLs.

The impact of fungi on soil protist communities in European cereal croplands - Florine Degrune; Kenneth Dumack; Masahiro Ryo; Gina Garland; Sana Romdhane; Aurélien Saghaï; Samiran Banerjee; Anna Edlinger; Chantal Herzog; David S. Pescador; Pablo García‐Palacios; Anna Maria Fiore‐Donno; et al. (Environmental Microbiology, 2024)
Protists, a crucial part of the soil food web, are increasingly acknowledged as significant influencers of nutrient cycling and plant performance in farmlands. While topographical and climatic factors are often considered to drive microbial communities on a continental scale, higher trophic levels like heterotrophic protists also rely on their food sources. In this context, bacterivores have received more attention than fungivores. Our study explored the connection between the community composition of protists (specifically Rhizaria and Cercozoa) and fungi across 156 cereal fields in Europe, spanning a latitudinal gradient of 3000 km. We employed a machine‐learning approach to measure the significance of fungal communities in comparison to bacterial communities, soil abiotic factors, and climate as determinants of the Cercozoa community composition. Our findings indicate that climatic variables and fungal communities are the primary drivers of cercozoan communities, accounting for 70% of their community composition. Structural equation modelling (SEM) unveiled indirect climatic effects on the cercozoan communities through a change in the composition of the fungal communities. Our data also imply that fungivory might be more prevalent among protists than generally believed. This study uncovers a hidden facet of the soil food web, suggesting that the benefits of microbial diversity could be more effectively integrated into sustainable agriculture practices.

Stakeholder perceptions of agricultural landscape services, biodiversity, and drivers of change in four European case studies - Monika Suškevičs; Katrin Karner; Claudia Bethwell; Florian Danzinger; Sonja Kay; Takamasa Nishizawa; Johannes Schuler; Kalev Sepp; Rando Värnik; Michael Glemnitz; Maaria Semm; Christina Umstätter; et al. (Ecosystem Services, 2023)

Assessing the habitat suitability of agricultural landscapes for characteristic breeding bird guilds using landscape metrics - Friederike Borges; Michael Glemnitz; Alfred Schultz; Ulrich Stachow (Environmental Monitoring and Assessment, 2017)

Regionalizing land use impacts on farmland birds - Michael Glemnitz; Peter Zander; Ulrich Stachow (Environmental Monitoring and Assessment, 2015)

Assessing the regional impacts of increased energy maize cultivation on farmland birds - Karoline Brandt; Michael Glemnitz (Environmental Monitoring and Assessment, 2014)